Artificial star (B) - Lim, Bonn Qian Jin (2014)
In crowded places where people gather for events such as concerts and exhibitions, there is high potential risk of chaos and eventual stampede, especially in the event of a blackout due to an interruption in power supply. In order to minimize the risks and prevent unnecessary loss of lives, the idea of artificial stars was conceived so that peace and order can be maintained to reduce the risk of an eventual stampede. As the name of the project implies, Artificial Stars represent the use of UAVs as a mean to ensure that the crowds stay organized and also guide them to safety.